2008
DOI: 10.1143/jjap.47.1101
|View full text |Cite
|
Sign up to set email alerts
|

Improved Fabrication Process for Enhancing Light Emission in Single-Layer Organic Light-Emitting Devices Doped with Organic Salt

Abstract: We investigated an improved method for enhancing light emission in single-layer organic light-emitting devices (OLEDs) stimulated by thermal and electrical annealing. In this study, we introduced fluorescent single-layer OLEDs doped with organic salt, tetrabutylammonium tetrafluoroborate (Bu 4 NBF 4 ). The annealing process consisted of simultaneously treated by thermal and electrical annealing in a noble gas environment filled with argon gas. Comparing with nonannealed OLEDs, we clearly observed homogeneous a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Organic and inorganic salt doping approach has also been applied to improve the performance of organic light emitting diode (OLED) [4][5]. Etoh et al reported that the performance of OLED doped with lithium perchlorate (LiClO 4 ) improved with the increase of electric field treatment [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Organic and inorganic salt doping approach has also been applied to improve the performance of organic light emitting diode (OLED) [4][5]. Etoh et al reported that the performance of OLED doped with lithium perchlorate (LiClO 4 ) improved with the increase of electric field treatment [5].…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al suggested that improvement of OLED performance could be achieved by simultaneous thermal and electrical treatment at relatively smaller electric field strength [4]. To the best of our knowledge, the effect of electrical treatment at different voltages on the performance of organic salt doped solar cell has yet to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…As another approach, doping of organic or inorganic salt has been known to enhance electron injection in PLEDs by the accumulation of ions near the cathode. [1][2][3][4][5][6] Appropriate biasing an electric field to PLEDs at a certain temperature invokes ions to move the counter electrodes. The base polymer of OLEDs could be poly(N-vinyl carbazole) (PVK), [1][2][3] poly(9,9 0 -dioctylfluorene) (PFO), 4) poly[2-methoxy-5-(2 0 -ethyl-hexyloxy)-1,4-phenylenevinylene] (MEH-PPV), 5) or poly(methyl metacrylate) (PMMA).…”
mentioning
confidence: 99%
“…The base polymer of OLEDs could be poly(N-vinyl carbazole) (PVK), [1][2][3] poly(9,9 0 -dioctylfluorene) (PFO), 4) poly[2-methoxy-5-(2 0 -ethyl-hexyloxy)-1,4-phenylenevinylene] (MEH-PPV), 5) or poly(methyl metacrylate) (PMMA). 6) In these studies, the salts utilized were tetra-n-butylammonium tetrafluoroborate (Bu 4 NBF 4 ), lithium bromide (LiBr), or lithium perchlorate (LiClO 4 ).…”
mentioning
confidence: 99%